The Implementation of High-Order Thinking Skills (HOTS) With the Integration of Tiktok Application to Improve The Students’ Speaking Skill - Mey Trisnawati Hulu; Kammer Tuahman; Arsen Nahum Pasaribu (Journal of Language Education (JoLE), 2024)
Speaking is one way that people can communicate with each other. Speaking is the medium of transaction between speaker and listener. The objectives of this research are 1) to find out the implementation of High Order Thinking Skills (HOTS) integrated with the Tiktok Application, and 2) to know the students’ responses toward the implementation of HOTS with the integration of the Tiktok Application. This research is Classroom Action Research (CAR) which was conducted by integrating High Order Thinking Skills with Tiktok Application to the eleventh-grade students of SMA Negeri 1 Alasa. The sample of this research is the eleventh grade of SMA Negeri 1 Alasa in the Academic Year 2023/2024. The result of the test showed that the students’ mean score on speaking skills in, the pre-test was 61.7, in the second cycle the mean score was 70.4, in the last cycle the mean score was 82.6. It showed that there is a significant mean improvement among cycles. The result of this research also shows that the students’ responses after being taught by using High Order Thinking Skills (HOTS) and TikTok applications are positive. It is suggested that teachers use the TikTok Application as an alternative to teaching speaking skills to the students in Senior High School to improve students’ speaking skills.